First description of MR mammographic findings in the tumor bed after intraoperative radiotherapy (IORT) of breast cancer - Wasser, Klaus; Schnitzer, Andreas; Engel, Dorothee; Krammer, Julia; Wenz, Frederik; Kraus-Tiefenbacher, Uta; Sütterlin, Marc; Schönberg, Stefan; Weisser, Gerald (Clinical imaging, 2012)
The aim was to investigate changes in the tumor bed on magnetic resonance mammography (MRM) after intraoperative radiotherapy (IORT) and whether they would limit the diagnostic value of posttherapeutic MRM. We retrospectively investigated 36 patients undergoing MRM after IORT (median interval 2.8 years, range 0.4-7.1). Wound cavities with fat necrosis were common after IORT (81%). They were associated with persisting contrast enhancement, i.e., enhancement was mostly seen irrespective of the posttherapeutic interval. It normally presented as rim enhancement and did not cause any diagnostic uncertainty if viewed together with other tissue characteristics. We do not expect a limited diagnostic value of MRM after IORT.